1995
DOI: 10.1099/0022-1317-76-2-451
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of human telomeric repeat sequences from human herpesvirus 6 and relationship to replication

Abstract: Here we examine by polymerase chain reaction amplification followed by cloning and sequence analyses selected regions of the human herpesvirus 6 (HHV-6) genome which contain human telomeric repeats (TTA-GGG). We determine the relative number, arrangement and orientation of the repeats in the unit length genome, in concatemeric replicative intermediates and in heterogeneous (het) regions. We also examine distribution of the repeats in the entire genome (159 kb) and their orientation relative to DNA packaging mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
64
0
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(67 citation statements)
references
References 37 publications
(32 reference statements)
2
64
0
1
Order By: Relevance
“…The unusual nature of these junctional clones is not understood. However, previous studies investigating the DNA structure of human herpesvirus type 6 (HHV-6) in infected cells also describe aberrant junctional clones generated by PCR amplification of the HHV-6 DR R -to-DR L junction (Gompels & Macaulay, 1995 ;Thomson et al, 1994). The studies offer no explanation for the anomalous junctions other than attributing them to possible PCR artefacts.…”
Section: Circular/concatemeric CCV Dna In Blood Of Latently Infected mentioning
confidence: 99%
“…The unusual nature of these junctional clones is not understood. However, previous studies investigating the DNA structure of human herpesvirus type 6 (HHV-6) in infected cells also describe aberrant junctional clones generated by PCR amplification of the HHV-6 DR R -to-DR L junction (Gompels & Macaulay, 1995 ;Thomson et al, 1994). The studies offer no explanation for the anomalous junctions other than attributing them to possible PCR artefacts.…”
Section: Circular/concatemeric CCV Dna In Blood Of Latently Infected mentioning
confidence: 99%
“…The unit-length DNA molecules are approximately 160 kb, composed of a 143-kb unique (U) segment flanked by left and right direct repeats (DR L and DR R , respectively) (19,24,27,46). The DRs are of sizes 8 to 10 kb in different viral isolates (2,19,24,46).…”
mentioning
confidence: 99%
“…On the other hand, the DR junction of CCV contained 11 to 17 bp of the right terminus of UL sequences following the DR R region (Gray et al 1999). While previous studies attributed the existence of nucleotides between DR regions to PCR artifacts (Thomson et al 1994, Gompels & Macaulay 1995, Gray et al 1999, our sequence analysis of the DR-PCR amplicon in the timecourse experiment showed that the same nucleotide sequences were present in all of the sequenced samples (data not shown). Further investigation is therefore necessary to examine the configuration of the DR junction of KHV.…”
Section: Discussionmentioning
confidence: 56%
“…3). In the case of HHV-6 which has a 10 kbp DR L and DR R region at the end of each genome terminus , the DR junction was sequenced using a PCR product, and aberrant junction sequences due to several nucleotide insertions or deletions were observed (Thomson et al 1994, Gompels & Macaulay 1995. On the other hand, the DR junction of CCV contained 11 to 17 bp of the right terminus of UL sequences following the DR R region (Gray et al 1999).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation